Trend analysis of pediatric urolithiasis prevalence from 1990 to 2021 in the BRICS - Zhang, Zhi-gang; Lin, Qing-cheng; Zhou, Qing-ying; Xu, Nai-fen; Zheng, Ding-qin; Pan, Qi-zhuang; Wang, Xin-jun; Xu, Ran (Frontiers in Pediatrics, 2025)
BackgroundThe increasing epidemiological trend of pediatric urolithiasis over the past three decades has brought it to the forefront of public health attention. An analysis of the disease burden in Brazil, Russia, India, China, and South Africa (BRICS) countries, which share common characteristics such as large population base and limited public health resources, will provide an important reference for global public health policy development. Therefore, this study aimed to investigate the trend of the prevalence of pediatric urolithiasis in BRICS countries during 1990–2021, which in turn will provide more valuable information for them and the world in the prevention and treatment of pediatric urolithiasis.MethodsIn this study, data were obtained from the Global Burden of Disease (GBD) database. The data were then statistically analyzed using the Joinpoint regression model, AutoRegressive Integrated Moving Average (ARIMA) prediction model, and subgroup analysis to assess trends in the prevalence of pediatric urolithiasis.ResultGlobally, the prevalence has been increasing every year, with the greatest increase in the 10–14 age group. Encouragingly, the Age-Standardized Prevalence Rate (ASPR) has shown a decreasing trend. The disease burden of pediatric urolithiasis is higher in India and Russia, with the prevalence in India and ASPR in Russia being the highest in the BRICS countries. In South Africa, there is a clear deficit in prevention and treatment in the 0–4 year age group. Additionally, although the burden of pediatric urolithiasis in Brazil is not currently severe, the trend is the fastest deteriorating among the BRICS countries. Finally, China has made significant progress in the prevention and control of pediatric urolithiasis over the past 30 years and is expected to continue this positive trend over the next 15 years.ConclusionThis in-depth analysis based on GBD 2021 provides a fresh perspective on the evolving burden of pediatric urolithiasis in BRICS countries over the last three decades. Our research provides valuable insights for policy makers and health care providers through in-depth analysis and scientific evaluation of the prevalence of pediatric urolithiasis using different statistical models. In addition, BRICS countries should develop targeted prevention strategies for at-risk populations and ensure the availability of effective treatments that are tailored to their national contexts while also reflecting global health trends and evidence.